ANALYSIS OF CRIME OF AGGRESSION IN 2026 UNITED STATES AND ISRAEL MILITARY STRIKES AGAINST IRAN - Dhuha Al Qodri; Harisman Harisman (NOMOI Law Review, 2026)
Although the prohibition on the use of force has been established in international law, contemporary armed conflicts continue to challenge its application, particularly regarding aggression. This study aims to analyze the qualification of the 2026 military strikes by the United States and Israel against Iran as a crime of aggression under the Rome Statute of the International Criminal Court (ICC), and to examine the use of self-defense and its implications for international law enforcement. The research employs a normative juridical method using statutory and conceptual approaches, supported by primary and secondary legal materials. The findings indicate that the military action fulfills the elements of the crime of aggression due to absence of United Nations Security Council authorization and lack of a valid self-defense justification. Furthermore, the study reveals that the expansion of self-defense, particularly preventive self-defense, poses a serious threat to international legal norms. The limitation of ICC jurisdiction weakens enforcement of international criminal law against powerful states. This study concludes that strengthening legal frameworks is essential to ensure accountability. It is recommended that international legal mechanisms be reformed to enhance consistency and fairness in addressing acts of aggression.